Anaerobic capacity of the upper arms in top-level team handball players - Kounalakis, S. N.; Bayios, I. A.; Koskolou, M. D.; Geladas, N. (International Journal of Sports Physiology and Performance, 2008)
Purpose: Handball is a sport with high anaerobic demands in lower body as has been indicated by Wingate test (WT) performed with the legs, but there are no data available concerning power production during a WT performed with the arms in handball players (HndP). Therefore, the purpose of this study was to explore the arm anaerobic profile of HndP during a WT. Methods: Twenty-one elite HndP and 9 physical education students (CON), performed a 30-s arm WT. Power production and muscle oxygenation were recorded. Results: Peak power (PP) as well as mean power (MP) was higher (P = .017 and 0.03, and ES = 1.00 and 0.86, respectively) for HndP (HndP PP: 7.6 ± 0.8 W·kg-1; CON PP: 6.7 ± 1.1 W·kg-1; HndP MP 5.3 ± 0.6 W·kg-1; CON MP 4.7 ± 0.9 W·kg-1) with no significant difference in fatigue index between the two groups. Muscle oxygen saturation (StO2) declined ~30% with exercise with no differences between groups. During recovery the HndP group had higher StO2 (P = .01, ES= 3.04), total hemoglobin and oxygenated hemoglobin compared with the CON group (P < .01 ES = 3.29 and 0.99, respectively). StO2 returned to resting values in 29.5 ± 2.3 s in HndP, whereas this variable did not recover after 2 min in CON. Conclusions: The arm anaerobic capacity of the HndP was "excellent," significantly higher than that by the control group. Moreover, HndP exhibited faster recovery of StO2 compared with the control group. The greater power output and the faster muscle reoxygenation of arms in HndP can be attributed to specific training adaptations related to high performance in handball.